DAMPAK KEPEMILIKAN MANAJER DAN UTANG TERHADAP KEMAMPULABAAN PERUSAHAAN - Dermawan, Iwan (Universitas Pendidikan Indonesia, 2013)
This empirical study aims to examine the relationship manager ownership (KSM) and debt (Lev), and the effect of stock manager ownership and debt to the company's ability of profitable (ROA). The study shows that managers stock ownership variables associated negative and significant with debt. While the effect of stock ownership by managers and debt to the company ability of profitable (ROA) negative and significant results.